"Sawer Panganten" Text in Sekejengkol Village, Cileunyi, Bandung Regency as a Cultural Asset: A codicological study - Saniro, Roma Kyo Kae; Adrianis, Adrianis (Environment-Behaviour Proceedings Journal, 2023)
The study of Sawer Panganten (SP) manuscript in Sekejengkol Village, Cileunyi, Bandung Regency, West Java, Indonesia, aims to describe and analyze the relevant data. This study uses descriptive analysis. This study uses a codicological approach. The researcher reveals the manuscript’s contents and functions through the text, such as marriage advice for the bride and groom. In conclusion, the study’s findings show that the SP manuscript is a tribal cultural asset because it explains the Sundanese culture and the meaning and function of texts and expresses cultural values as an alternative to cultural development.